Biocompatibility and corrosion resistance of metallic biomaterials - Ali, S. (De Gruyter Open Ltd, 2020)
Biomaterials play a significant role in revolutionizing human life in terms of implants and medical devices. These materials essentially need to be highly biocompatible and inert to the human physiological conditions. This paper provides an in-depth, critical and analytical review on the previous research work and studies conducted in the field of metals and alloys used as implant materials including stainless steel, titanium and its alloys, cobalt chromium and others. Since the manufacturing of medical implants relies on selected grades of biomaterials, metals play a significant role in biomaterials market. This paper focuses on highlighting some basic principles of manufacturing implant materials underlying composition, structure and properties of these materials. Finally, attention is also given to the role of these implant materials on the betterment of human life in terms of their failures by critically analysing these materials. Â© 2020 De Gruyter. All rights reserved.